The application of x-rays in radiology: from difficult and dangerous to simple and safe - Kemerink, Martijn; Dierichs, Tom J.; Dierichs, Julien; Huynen, Hubert; Wildberger, Joachim Ernst; van Engelshoven, Jos M. A.; Kemerink, Gerrit J. (American journal of roentgenology, 2012)
Choose - Top of pageABSTRACT <<ExperimentsResults in PerspectiveSummaryReferencesCITING ARTICLES OBJECTIVE. This article will provide an assessment of the application of x-rays in the early days of radiology, which is an excellent way to come to value the convenience and safety of modern x-ray systems. CONCLUSION. The gas tubes that were originally applied for x-ray production were very unstable because of variations in the tube’s vacuum. In an effort to understand some of the problems of these tubes and the high occupational exposure that was indirectly caused by the tubes’ erratic behavior, we measured x-ray output rates as a function of the gas pressure inside the tube. The pressure range for the optimal production of x-rays, using an original Ruhmkorff inductor as a high-voltage generator, was found to be narrow. With the vacuum changing over time, this might explain the many photographs from the first years of radiology with operators watching their unshielded tube, either with bare eyes or with a fluoroscope, and their own hand as a test object. This practice often led to severe damage of the hands and to many early deaths due to cancer. Today, after a century of technologic development of x-ray tubes and associated equipment, the total average effective dose of workers in radiology can be close to natural background levels.